Pengaruh Pengembangan Pegawai, Komitmen Dan Kepuasan Kerja Terhadap Kinerja Pegawai Dalam Implementasi Online Sistem - Ena Sugriana; Daenulhay Daenulhay; Imam Muttaqin; Cahyani Kurniastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the magnitude of the influence of employee development variables, commitment, and job satisfaction on employee performance variables in the implementation of the online system at SMAN 23 Tangerang Regency. The vision of SMA Negeri 23 Tangerang Regency is the realization of graduates who are characterized, intelligent and competitive, while the mission of SMAN 23 Tangerang Regency is: To form a generation of intellectual intelligence, emotional intelligence, creative, skilled and dedicated and have high social sensitivity, motivate students to become individuals independent so that academic and non-academic achievements can be realized, forming students who are able to compete in the global era, developing faith and piety so that they become a source of wisdom in acting, increasing the ability and professionalism of teachers and employees as well as developing systems, organizations, administrative and participatory management through science and technology. technology to create quality schools. The method used in this study is a quantitative method, with 44 employees as respondents at SMAN 23 Tangerang Regency. Data analysis with multiple linear regression model, so as to obtain the results of employee development and job satisfaction have an effect on employee performance at SMAN 23 Tangerang Regency. Keywords: Employee Development, Commitment, Job Satisfaction, and Employee Performance